2021
DOI: 10.3389/fimmu.2021.680146
|View full text |Cite
|
Sign up to set email alerts
|

Could β-Lactam Antibiotics Block Humoral Immunity?

Abstract: It has been reported that treatment with β-lactam antibiotics induces leukopenia and candidemia, worsens the clinical response to anticancer immunotherapy and decreases immune response to vaccination. β-lactamases can cleave β-lactam antibiotics by blocking their activity. Two distincts superfamilies of β-lactamases are described, the serine β-lactamases and the zinc ion dependent metallo-β-lactamases. In human, 18 metallo-β-lactamases encoding genes (hMBLs) have been identified. While the physiological role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 88 publications
1
2
0
Order By: Relevance
“…The results of C5 enrichment analysis in the high immune score group suggested that the infiltration of immune cells in the TME of CRC might be related to the following biological functions: amide binding, response to wounding, endosomal part, calcium ion transmembrane transport, and endocytic vesicle (Fig 2D). The biological function of amide binding was of the highest NES in the high immune score (Fig 2C, S1 Appendix), which indicated that this gene set might regulate the immune response in patients with CRC by inducing related amide binding, that was consistent with the previous research [43].…”
Section: Results Of Gene Set Enrichment Analysis (Gsea)supporting
confidence: 89%
“…The results of C5 enrichment analysis in the high immune score group suggested that the infiltration of immune cells in the TME of CRC might be related to the following biological functions: amide binding, response to wounding, endosomal part, calcium ion transmembrane transport, and endocytic vesicle (Fig 2D). The biological function of amide binding was of the highest NES in the high immune score (Fig 2C, S1 Appendix), which indicated that this gene set might regulate the immune response in patients with CRC by inducing related amide binding, that was consistent with the previous research [43].…”
Section: Results Of Gene Set Enrichment Analysis (Gsea)supporting
confidence: 89%
“…In vitro studies showed that some β-lactam antibiotics, namely third-generation cephalosporins and ampicillin, inhibit metallo-β-lactamase proteins SNM1 (sensitive to nitrogen mustard) A & B and SNM1C/Artemis protein complex. The authors of the publication [71] claim that β-lactam antibiotics (cephalosporins, ampicillin) can block the SNM1C/Artemis protein in humans, causing transient immunodeficiency.…”
Section: Of 12mentioning
confidence: 99%
“…Th1, Th2, and T reg [ 11 ], and it is known in mice that antibiotic-driven dysregulation of the GM can modulate immune responses to vaccines in early [ 33 ] and in late life [ 34 ]. Ampicillin has been hypothesized to block humoral vaccine responses in humans, because its blocking of a specific protein the lack of may induce a transient immunodeficiency [ 35 ]. Also, bacterial flagellin stimulation of Toll-like receptor 5 (TLR5) is needed to drive antibody production after influenza vaccination [ 36 ].…”
Section: Introductionmentioning
confidence: 99%